Biomarkers for Huntington's disease - promises and challenges - Tabrizi, Sarah (Henry Stewart Talks, 2013)
Summary of the genetic, pathophysiology and clinical features of Huntington's disease, Potential drug targets in development for Huntington's disease, The importance of biomarkers in Huntington's disease, Current biomarkers in development in Huntington's disease